KUALITAS LAYANAN BANDAR UDARA INTERNASIONAL SULTAN HASANUDDIN TERHADAP PENGEMBANGAN PARIWISATA DI PROVINSI SULAWESI SELATAN - Milawaty Waris (Jurusan Teknik Sipil Universitas Bangka Belitung, 2022)
The development of air transportation activities around the world has increased the demand for airport services and for more efficient aircraft, passenger or baggage service processes. The airport is a key artery for the development of a nation. As time goes by, in the era of Society 5.0, means of transportation are growing and following technological developments. This study aims to determine how big the relationship between the quality of air transportation services at Sultan Hasanuddin International Airport on tourism development in South Sulawesi Province. In this study, path analysis was used with the help of the SPSS 25 software program through primary and secondary data collection. Based on the results of the analysis, the number of respondents as many as 100 respondents who participated in filling out the questionnaire, obtained the standard deviation value of each variable for waiting rooms of 5.143, for parking spaces of 3,775, for artificial tourism exploration parks of 3,401 and for tourism development of 5,839. The results of the correlation analysis test show that Ho is accepted while H1 is not accepted. correlation analysis obtained the value of r on the correlation ryx1x2x3 of 0.923. The value of r 0.923 0.837 indicates that the level of relationship between the three variables has a very strong relationship. In the sense that the variable passenger waiting room (X1), parking space (X2), and an artificial exploration park at the airport (X3) have assumptions that are simultaneously and significantly related to the tourism development variable (Y)